Unsuccessful transitions: Understanding dropout from the athletes` perspective - Andronikos, G.; Westbury, T.; Martindale, R. J. J. (Athens Journal of Sport, 2019)
Limited studies have investigated the experiences of athletes who did not make it? to elite level.To target this research gap,this study accessed and investigated this hard to reach populationin order to understand the developmentand transition experiences of athletes who did not manage to negotiate successfully the junior to senior elite transition. Aqualitative methodology was utilised and six athletes were interviewed. Inductive analysis showed that an unsuccessful transition from junior to senior level is highly individual and is attributed to a combination, rather than a single factor. The factors emerging from the work, which can increase the risk of athletes dropping out included: poor communication; inappropriate support;balancing a dual career without support or with excessive pressure;and a win focus environmentduring the development stage.Implications for coaches and policy makers with regards to impacting positively on both the transition experience itself and earlier foundation experiences are discussed further.